(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article will tell you how to learn English and get a certificate quickly and easily, how to reach level 0 to B2 in a short time. The article provides very important and necessary recommendations for language learners. It will show you how to achieve a good level in a short time, that is, in 6 months, using modern science and technology.